THE ANALYSIS OF SOME LOADING AND PHYSIOLOGICAL VARIABLES ON DIFFERENT INTENSE INTERVAL "FAST-BREAK AND QUICK RETREAT" EXERCISE IN TEAM HANDBALL - Primož Pori; Uroš Mohorič; Marko Šibila (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2010)
The aim of the study was to analyze response of the players in some physiological and loading variables on different intense interval "fast-break and quick retreat" exercise in Team handball. A group of fifteen well trained team handball players of the third Slovenian handball league (age: 23,3 ± 3,3 yr, height: 184 ± 2 cm, body weight: 87 ± 7,3 kg, training experience: 7,8 ± 3,6 yr) participated in the present study. The sample of variables consisted of six physiological and five loading variables. Differences between the average arithmetic mean values of loading as well as physiological variables were tested with the General linear model of repeated measures. It seems that the physiological response of players during the interval "Fast-break with quick retreat" 3vs3 is the most closely related with the results of similar studies, made on the sample of the team handball players during the handball matches. The specific interval handball exercises that we use in present study could be very suitable from the specificsendurance preparation aspect.